Assessing India's Nutraceuticals and their Impact on Disease Prevention (Bhartiya Knowledge Systems, 2024)
"Nutraceutical," a word derived from "nutrition" and "pharmaceutical" was found to be a potential nutritional and safety profile that has many health benefits in human lifestyle. The use of nutraceuticals for food, nutrition, and pharmaceutical purposes has gained popularity, particularly in India, as a practical way to maintain maximum health. Since 2500-500 BC, the acceptance of modern nutraceuticals in India has been influenced by the popularity of Ayurveda, the traditional Indian medical system. The numerous varieties of Indian medicinal plants that were noted as being useful for health are evaluated as far as how they relate to various illness prevention in this review article.